WIDHI ÚRADDHA (Kajian Veda dan Úaiwa Siddhanta) - Surada, I Made (VYAVAHARA DUTA, 2012)
AbstractIn Hinduism teaching, confidence in the existence of super power of natural soul by Veda teaching. Single traditional idea the existence of statement expressing that Veda holy book Hinduism. As holy book of Hinduism, hence Veda believed and guidance by Hindu people as single the source of needed information and tuition in everyday life and or for the time of is certain.Veda book have various - as religious idea growth phase. In Veda there are materialization polytheism marking, organized polythe spreading Teaching Veda through wide of area and also require very long time, because area broadness and passed by time length, hence just Veda face earn change as according to passed by time and room, but its remain to Veda esensi. In Hinduism growth and spreading in Bali, realization arrange its execution is constituted by source of Tattwa teaching specially Sivatattwa papyruss. In papyrus art, year praised as Bhatara Siva, which its source always we meet in religion art, saa, worship, upakara, And altars Arca-arca. Teaching like this conceived of [by] Sivasiddhanta teaching. God in Veda called by Agni or Indra or Waruna, in God Upanisad called by Brahman, hence in Hinduism God Bali is called by the The Hyang Widhi or Siwa. Esensi Teaching Believing in god in Tattwa Siwa equal to Believing in god teaching in Veda. realized Teaching Siwa Tattwa in life believe in Hindi in Bali, henotheisme, monoisme and monotheisme.Existence of equality of principality between Believing in god teaching in Veda and Saivasiddhanta. God Who are Single The most in which is many, what is many in Single. Sat Agni, Yama, Matarisvan. Siva Mahadeva, Isvara, Paramesvara etcetera, and Deity itself is Siwa. In Veda even also also in God Saivasiddhanta one with all is existing. Key Words : Widhi Sraddha, Veda, Úiwasiddhànta